Frequent mental distress among adults in the United States and its association with socio-demographic characteristics, lifestyle, and chronic health condition: 10.55131/jphd/2022/200112 - Rashid, Mamunur; Islam, M. Mazharul; Li, Aiping; Shifa, Naima (Journal of Public Health and Development, 2022)
Frequent mental distress (FMD) is a measure of poor mental health days for at least 14 days out of 30 days. It is one of the important dimensions of the health-related quality of life. The underlying causes of FMD are diverse. However, the issue has not been explored extensively due to the lack of reliable data on mental health. The aim of this study was to examine the level and trends of FMD among the adults of the United States (US) and identify the socio-demographic, lifestyles, and chronic health outcomes related correlates of FMD. The data for the study was obtained from the publicly available 2019 Behavioral Risk Factor Surveillance System (BRFSS) in the US, covering a large sample of 418,268 adult respondents from all the 50 states and participating territories. Respondents from each state and territory were identified by selecting the telephone number from the telephone directory following a systematic sampling design. To examine the trends in the prevalence of FMD, data from the 2010-2018 BRFSS were also utilized. Both descriptive and inferential statistical techniques, including multiple logistic regression models were employed to analyze the data. Results indicated that about 12% of the adults in the US experienced FMD, and the prevalence of FMD is increasing over time. Females, students, adults aged below 35 years, multiracial, less educated, single, low income, and underweight individuals were found to have a higher risk of FMD. FMD was found to be significantly associated with unhealthy lifestyles and chronic health conditions. This study findings highlight the importance of interventions for mental health promotion and mental illness prevention, substance use prevention, screening and treatment services of FMD, and increased provision of resources to address social and economic determinants of FMD.